Estimation of the value of convenience in taking influenza antivirals in Japanese adult patients between baloxavir marboxil and neuraminidase inhibitors using a conjoint analysis. (1st January 2021) - Hosogaya, Naoki; Takazono, Takahiro; Yokomasu, Akira; Hiroi, Shinzo; Ikeoka, Hidetoshi; Iwasaki, Kosuke; Takeshima, Tomomi; Mukae, Hiroshi
Abstract: Aims: Estimating the monetary value of the convenience of using influenza antivirals approved in Japan from a patient perspective using a conjoint analysis. Methods: An online survey (August 2020) was performed on individuals aged 20–64 years living in Japan who had taken oral or inhalant antivirals for influenza treatment in the 2018/19 or 2019/20 seasons. Efficacy and safety were assumed to be equivalent among the antivirals. The attributes for the conjoint analysis included route (oral or inhalant), duration, frequency of administration, and out-of-pocket expenses. A conditional logit model was applied as a baseline model. The monetary value of each attribute was calculated by comparing the same utility of the linearly interpolated level of the out-of-pocket attribute. Another survey to determine the experiences of the latest antiviral intake was also conducted on the same respondents. Results: Of the respondents, 1, 550 were men and 1, 587 were women. The monetary value for oral antivirals was estimated to be higher, saving JPY 741 (USD 7.06, as of August 2020), compared with inhalant. Regarding the length and frequency of administration, five days corresponds to an increase of JPY 2, 072, compared with one day, and twice a day corresponds to a JPY 574 increase compared to once a day. Conclusions: The results suggest that – among the antivirals approved in Japan – the monetary value of the utility is the highest in the single dose oral antiviral, baloxavir marboxil (baloxavir). Although the drug cost was highest in baloxavir among the brand antivirals, the difference in the value of utility for influenza patient was estimated to be larger than the difference in the drug costs. Limitations: Although individuals with diverse attributes from all over the country were included in the survey, they are not necessarily a representative population of the Japanese society.